1992
DOI: 10.1177/014920639201800404
|View full text |Cite
|
Sign up to set email alerts
|

Mediating and Moderating Effects in Job Design

Abstract: A test of the complete Job Characteristics Model (Hackman & Oldham, 1976, 1980) was conducted, with particular emphasis on the little-investigated mediating and moderating effects specified by the model. Three hundred lower level managers provided questionnaire data. Results indicated that the model's psychological states generally mediated the relationship between job characteristics and outcomes. However; the correspondence between the job characteristics and the states was not precisely that specified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 32 publications
6
105
1
9
Order By: Relevance
“…Whereas Oldham (1975, 1980) suggested that the critical psychological states would each independently act as mediators, later work suggested that the true mediation model is different (Johns et al, 1992;Oldham, 1996 Hypothesis 3: Experienced meaningfulness, experienced responsibility, and knowledge of results will mediate the relationships between (a) autonomy, (b) skill variety, (c) task identity, (d) task significance, and (e) feedback from the job and the behavioral and attitudinal outcomes.…”
Section: Testing the Job Characteristics Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Oldham (1975, 1980) suggested that the critical psychological states would each independently act as mediators, later work suggested that the true mediation model is different (Johns et al, 1992;Oldham, 1996 Hypothesis 3: Experienced meaningfulness, experienced responsibility, and knowledge of results will mediate the relationships between (a) autonomy, (b) skill variety, (c) task identity, (d) task significance, and (e) feedback from the job and the behavioral and attitudinal outcomes.…”
Section: Testing the Job Characteristics Modelmentioning
confidence: 99%
“…Fried and Ferris (1987, p. 305) examined only corrected correlations between the motivational work characteristics, the critical psychological states, and outcomes and explicitly noted that "bivariate correlational analysis cannot provide a specific test of the mediating hypothesis and is less appropriate than other more sophisticated statistical tests." Using more sophisticated techniques, we performed the first metaanalytic test of these mediational predictions.Whereas Oldham (1975, 1980) suggested that the critical psychological states would each independently act as mediators, later work suggested that the true mediation model is different (Johns et al, 1992;Oldham, 1996 Hypothesis 3: Experienced meaningfulness, experienced responsibility, and knowledge of results will mediate the relationships between (a) autonomy, (b) skill variety, (c) task identity, (d) task significance, and (e) feedback from the job and the behavioral and attitudinal outcomes. …”
mentioning
confidence: 99%
“…In line with the theodzing of Bono and Judge (2003) and Shamir et al (1993), we hypothesize that employees of tratisformadonal leaders find their jobs more meaningful and, thus, become immersed iti their jobs, that is, they achieve a state of flow (Johns, Xie, & Fang, 1992 Work-related flow is defined as a short-term peak experience at work (Bakker, 2005(Bakker, , 2008 and is characterized by a high amount of enjoyment, total concentration, and a condnuous interest in one's work. In line with recent attention on positive organizational behavior research (Bakker & Schaufeli, 2008), we attempted to test a mediadon model wherein both posidve individual work experiences, such as work-related flow, and posidve career outcomes (i.e., employability enhancement) were included.…”
Section: Learning Value Of the Jnh And Kmployahilitymentioning
confidence: 91%
“…While Hackman andOldham (1975, 1976) originally proposed that these three critical psychological states were independent mediators that must all be present for desired work outcomes to be produced, more recent research has suggested that experienced meaningfulness was the best mediator between the motivational characteristics and work outcomes (Johns, Xie, & Fang, 1992). This proposition was further supported by Humphrey et al (2007) in the first meta-analytic test of the mediational role of psychological states between job characteristics and job outcomes.…”
Section: Motivational Approach To Work Designmentioning
confidence: 98%